1993
DOI: 10.1177/0148607193017003231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Liquid Diet With and Without Soluble Fiber Supplementation on Intestinal Transit and Cholecystokinin Release in Volunteers

Abstract: The effect of adding fiber to liquid formula diets on gastrointestinal transit is still controversial. Different fiber types (soluble vs insoluble) and different methodology of transit time measurements yielded variable results. Factors affecting transit include colonic fermentation, neural, and hormonal factors. We have therefore compared the effects of a standardized normal diet and two liquid formula diets with and without supplementation of a soluble fiber (21 g/L) on orocecal transit time measured by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 21 publications
1
40
0
Order By: Relevance
“…Dietary fibers such as guar gum (GG) were found to effectively increase fullness and satiety resulting in reduced energy intake (Evans & Miller, 1975;Pasman et al, 1997), eg by decreasing the rate of gastric emptying and small intestinal transit (Harju, 1985;Wilmshurst & Crawley, 1980;Blackburn et al, 1984a). However, other more recent studies found no effects of GG supplementation on gastric emptying and=or intestinal transit rate (Rydning et al, 1985;Lavin & Read, 1995;Meier et al, 1993). It has also been observed that GG ingestion may modify glucose absorption (Blackburn et al, 1984b) resulting in a prolonged feeling of satiety (Leeds, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary fibers such as guar gum (GG) were found to effectively increase fullness and satiety resulting in reduced energy intake (Evans & Miller, 1975;Pasman et al, 1997), eg by decreasing the rate of gastric emptying and small intestinal transit (Harju, 1985;Wilmshurst & Crawley, 1980;Blackburn et al, 1984a). However, other more recent studies found no effects of GG supplementation on gastric emptying and=or intestinal transit rate (Rydning et al, 1985;Lavin & Read, 1995;Meier et al, 1993). It has also been observed that GG ingestion may modify glucose absorption (Blackburn et al, 1984b) resulting in a prolonged feeling of satiety (Leeds, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…The putative mechanisms of L. rhamnosus GG action may include stimulation of the cell proliferation rate of bowel epithelial cells, enhanced secretion of protective mucins leading to reduced adherence of enteropathogenic bacteria to the bowel wall, inhibition of bacterial translocation into the tissues, and stimulation of local and systemic immune response to pathogens (Mattar et al, 2001;Banasaz et al, 2002;Khaled et al, 2003;Mack et al, 2003;Vaarala, 2003). Partially hydrolysed guar gum fibre may also reduce duration of diarrhoea (Homann et al, 1994;Alam et al, 2000) and prolong the colonic transit time (Meier et al, 1993). Thus, hypothetically, besides themode of 5-FU administration, the frequency and severity of chemotherapy-associated gastrointestinal adverse events might be influenced by the diet and the bowel microbial flora.…”
mentioning
confidence: 99%
“…It was also reported that PHGG prolonged colon transit time [31], by which the hydrolyzed form of guar gum offered the potential to reduce diarrhea and to positively influence the osmotic balance in the colon through increased fermentation by anaerobic bacteria that yield SCFA [32]. The effects of a standardized normal diet and two liquid formula diets with and without supplementation of PHGG (21 g/l) on orocecal transit time, colonic transit time, bowel movements, and stool consistency were studied in 12 healthy male volunteers [31], in which the diets were consumed in a randomized order, each one for 7 days. The addition of PHGG did not affect orocecal transit time.…”
Section: Phgg Demonstrates Preclusive Effect Against Diarrhea Throughmentioning
confidence: 87%